Catalytically activated stainless steel plates for the dehydrogenation of perhydro dibenzyltoluene - Solymosi, Thomas Andrew; Auer, Franziska; Dürr, Stefan; Preuster, Patrick; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2021)
Hydrogen storage and transport via Liquid Organic Hydrogen Carriers (LOHC) is gaining increasing attention. In this study, we present catalytically activated stainless steel plates as a promising alternative to the commonly used pellet catalysts for the dehydrogenation of perhydro dibenzyltoluene (H18-DBT). These plate catalysts promise better heat transport to the active sites. For improved performance, we modified our Pt/alumina plate catalysts by using i) platinum sulfite impregnation and ii) post-treatment with (NH4)2SO4. Post-treatment with (NH4)2SO4 resulted in a less active catalyst with lower formation of high-boiling side products compared to the S-free plate catalyst. Catalysts prepared with platinum sulfite showed both >35% higher activities and 90% reduction in high-boiler formation compared to the S-free plate catalysts. Our findings pave the way for the development of catalytically activated heat transfer plates that would allow the incorporation of LOHC dehydrogenation units into the geometry of future high temperature fuel cell stacks.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Dehydrogenation; LOHC; Perhydro dibenzyltoluene; Plate catalysts; Selective poisoning

Enhancing the power density of hydrogen release from LOHC systems by high Pt loadings on hierarchical alumina support structures - Auer, Franziska; Solymosi, Thomas Andrew; Erhardt, Chris; Cuadrado Collados, Carlos; Thommes, Matthias; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2025)
In this contribution, a step change in the power density of hydrogen release from LOHC systems is presented. This could be achieved by the use of hierarchical alumina supports in combination with high Pt loadings. Here, a demonstration was carried out for the catalytic dehydrogenation of perhydro dibenzyltoluene (H18-DBT). In the course of our study, different alumina support materials were characterized and loaded with 0.3, 0.6, 0.9 and 1.2 wt%Pt, respectively. It was found that a specific bimodal pore structure with a large pore volume in both, the mesoporous range between 10 and 25 nm and the macroporous range between 500 and 1000 nm, enabled high Pt-based productivities even at Pt loadings, four times higher than that of the current technical standard. This gives access to a substantially improved volumetric power density of the respective catalyst. In batch dehydrogenation experiments with a 1.5 mm pellet and a Pt loading of 0.9 wt%Pt, a doubling of volumetric power density could be achieved compared to the technical 0.3 wt%Pt standard material (Clariant, Elemax D102). Our analytical work elucidated that this highly relevant increase can be related to a faster mass transfer resulting from the special pore structure of the catalyst support and to a better Pt distribution on the support resulting in a thinner egg-shell layer. Using the optimized catalyst materials in continuous fixed-bed dehydrogenation experiments higher gas hold-up in the reactor and dewetting of the catalyst surface become additional aspects that influence the overall observed catalyst performance.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Catalyst; Dehydrogenation; LOHC; Power-density; Reactor; Space-time-yield

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene† - Schörner, Markus; Solymosi, Thomas Andrew; Raczka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt–alumina on steel beads, b) Pt–alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with P
Keywords: Hydrogen storage; Inductive heating; LOHC; Platinum; Perhydro benzyltoluene